Inter‐ and Intra‐Device Variation and Correlation of Hyperfine Interactions in Micron‐Scale Organic Light‐Emitting Diodes - A. Mena; R. Geng; W. J. Pappas; F. Maasoumi; D. R. McCamey (Advanced Sensor Research, 2024)
Abstract The spin‐dependent properties of opto‐electronic devices, such as sensors, displays, and photovoltaics, are a key contributor to performance metrics such as sensitivity and efficiency. As these devices are pushed to smaller scales, an understanding of how the microscopic variations in their spin‐dependent properties impact the macroscopic scale is becoming increasingly important. In this study, the hyperfine interactions of charge carriers are investigated within a series of co‐polymer thin‐film organic light‐emitting diodes (OLEDs), with each set of devices having a different physical size. Using spatially resolved measurements, significant variation in hyperfine interactions within microscopic thin‐film OLEDs is found. The domain size of spatially correlated hyperfine regions is characterized within these devices, finding characteristic scales of several microns. Finally, multiple device averaged magneto‐electroluminescence (MEL) responses from arrays of identical devices are simultaneously measured, to probe the influence of microscopic variation on the macroscopic hyperfine properties. It is found that smaller devices typically display a smaller device‐averaged hyperfine interaction. These findings shed light on the importance of spin dynamics in optoelectronic devices and provide insights for improving their performance.